(untitled) - Nedeliak, Ivan; Nedeliakova, Eva (Doprava a spoje, 2009)
This article deals with continuity of the quality processes in the railway transport and data transmission through traction line. There are defined current systems used in overhead contact lines in the Slovak republic, data transmission in line with high voltage and safety at work with traction line. The article describes advantages of data transmission through traction line and its utilization in the railway operation and monitoring of processes.